2022
DOI: 10.3389/fcvm.2022.922357
|View full text |Cite
|
Sign up to set email alerts
|

Graft preservation confers myocardial protection during coronary artery bypass grafting

Abstract: BackgroundDuring on-pump coronary artery bypass grafting (ONCAB), graft flushing for distal anastomoses testing also perfuses the downstream myocardium. This single-center retrospective study evaluated the impact of specific preservation solutions on myocardial protection during ONCAB.Materials and methodsBetween July 2019 and March 2020 either DuraGraft (DG) or 0.9% Saline/Biseko (SB) was applied to 272 ONCAB. Overall, 166 patients were propensity-matched into two groups. Cardiac enzymes [high-sensitive Tropo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…Dura-Graft®, a novel specific solution, demonstrated promising results and was designed to address the aforementioned shortcomings. With growing awareness on the topic of VGF, several studies have confirmed the positive effects on the vessel wall integrity and the ischemia-reperfusion complex, provided that the solutions are disposable and fundable [12,13]. The same aspect accounts for the type of harvesting.…”
mentioning
confidence: 99%
“…Dura-Graft®, a novel specific solution, demonstrated promising results and was designed to address the aforementioned shortcomings. With growing awareness on the topic of VGF, several studies have confirmed the positive effects on the vessel wall integrity and the ischemia-reperfusion complex, provided that the solutions are disposable and fundable [12,13]. The same aspect accounts for the type of harvesting.…”
mentioning
confidence: 99%